2017
DOI: 10.1155/2017/3678017
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac Hemostasis and Fibrinolysis Parameters in Patients with Atrial Fibrillation

Abstract: Aims To identify intracardiac hemostasis or fibrinolysis abnormalities, which are associated with atrial fibrillation (AF) and increase the risk of thromboembolism. Patients and Methods Patient group consisted of 24 patients with AF and control group included 14 individuals with other supraventricular tachycardia undergoing transcatheter radiofrequency ablation. Blood samples were drawn from the femoral vein (FV), left atrium (LA), and left atrial appendage (LAA) before the ablation procedure. Fibrinogen, fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Previously, our group measured hemostasis activation in blood samples obtained sequentially from different sites including the femoral vein, the left atrium, and the left atrial appendage without any ablation therapy. In this earlier work, which was completed in a different patient cohort than the present study, we demonstrated that transseptal puncture itself is a significant signal for further hemostasis activation [13]. e main focus of the present study was to evaluate the effect of left atrial ablation per se; therefore, blood samples were obtained from the LA before the 1st and immediately after the last energy application.…”
Section: Fibrinolysis Activation During Pvi Limited Data and Conflicmentioning
confidence: 75%
See 2 more Smart Citations
“…Previously, our group measured hemostasis activation in blood samples obtained sequentially from different sites including the femoral vein, the left atrium, and the left atrial appendage without any ablation therapy. In this earlier work, which was completed in a different patient cohort than the present study, we demonstrated that transseptal puncture itself is a significant signal for further hemostasis activation [13]. e main focus of the present study was to evaluate the effect of left atrial ablation per se; therefore, blood samples were obtained from the LA before the 1st and immediately after the last energy application.…”
Section: Fibrinolysis Activation During Pvi Limited Data and Conflicmentioning
confidence: 75%
“…Postablation blood samples were collected through the LA sheath after removal of the ablation catheter once the last ablation was finished. Forty-five ml blood samples were drawn from which the first 15 ml of blood was discarded in order to exclude intrasheath hemostasis activation [13]. Blood samples were collected into vacutainer tubes (tubes containing 0.109 M sodium citrate), tubes containing CTAD (buffered citrate, theophylline, adenosine, and dipyridamole), and tubes containing no anticoagulant (serum tubes with polymer gel separator, SST; Becton Dickinson, Franklin Lakes, NJ).…”
Section: Blood Sampling and Laboratory Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study investigating intracardiac hemostasis or fibrinolysis abnormalities in AF patients, the SFMC levels did not show significant changes compared with controls. 31 In another study in patients with AF taking warfarin therapy, elevated SFMC levels during anticoagulant treatment were not useful as predictors of thromboembolic events. 32 To our knowledge, this is the first large real-world study investigating the role of SFMC for risk stratification and prediction of adverse cardiovascular events and mortality in AF patients receiving VKA therapy.…”
Section: Discussionmentioning
confidence: 95%
“…On the contrary, uninterrupted administration of dabigatran in randomized trials [17,18] was associated with significantly less bleeding complications as compared with continuous VKA administration. Recent studies suggest that in AF patients, intracardiac blood sampling revealing local conditions of hemostasis activation and endothelial damage might reflect the thrombogenic state more precisely, as blood sampling from the systemic circulation might not be able to show subtle, but significant local changes [19][20][21][22]. However, potential differences between various OACs to inhibit hemostasis activation in the settings of left atrial ablation, most probably due to the difficulty of intracardiac sampling, have not been directly tested from intracardiac blood samples as of yet.…”
Section: Introductionmentioning
confidence: 99%